Random blood glucose level as predictor of cognitive impairment in elderly - Amnur R. Kayo; Acitta Raras Wimala; Natalya Angela; Izzura binti Abdul Rashid (Universa Medicina, 2012)
Background     Nutritional deficits have been linked to poor cognitive function and are highly prevalent in the elderly. Several factors associated with cognitive function have been studied, but the results were inconclusive. The objective of this study was to determine the relationship between blood glucose level and cognitive impairment in the elderly. MethodsA cross-sectional study was conducted and a total of 109 elderly were included in the study. Research subjects were selected using consecutive non-random sampling from the Tebet sub-district in South Jakarta. Random blood glucose level was assessed using glucose strips (Nesco). Cognitive function was measured with the Montreal Cognitive Assessment (MoCA) and Informant Questionnaire on Cognitive Decline in Elderly (IQCODE) questionnaire. The relationship between blood glucose levels and cognitive function was analyzed by means of multiple linear regression analysis. ResultsThe mean age of the elderly was 67.95 ± 6.42 years, length of formal education was 10.12 ± 5.88 years, and mean random blood glucose level was 137.41 ± 70.25 mg/dL. Multiple regression analysis showed that length of formal education (â= 0.769; p=0.000) and random blood glucose levels (â=0.016; p=0.014) were significantly associated with cognitive function. Conclusion Cognitive function is negatively affected by high blood glucose, thus random blood glucose level can be used to predict cognitive impairment.